One pot room temperature synthesis of robust gold nanochains - Biradar, Satish C.; Kulkarni, Mohan G. (RSC Advances, 2013)
We report a room temperature reduction and stabilization of gold nanoparticles (AuNPs) from auric chloride in the presence of 1.5 and 3 mM linear poly(amidoamine) (PAmAm), which leads to 1D assembly of AuNPs. At higher concentrations, isolated AuNPs are formed. Detailed investigations show that the morphology is governed primarily by pH rather than concentration. This is the first report to demonstrate the stability of nanochains against pH switching. The nanochains are robust as revealed by stability at higher temperature, salt concentration, thiol exchange, and would be useful in developing electronic devices for biological applications.